2014
DOI: 10.2203/dose-response.13-039.jargin
|View full text |Cite
|
Sign up to set email alerts
|

Chernobyl-Related Cancer and Precancerous Lesions: Incidence Increase Vs. Late Diagnostics

Abstract: The reported incidence of thyroid cancer in children and adolescents in Soviet Union before the Chernobyl accident was lower than in other developed countries. This is not clearly recognizable from the literature because comparisons of the high incidence figures 4 years after the accident and later have been made with those from the first years after the accident, when the registered incidence had already started to increase. Considering the low pre-accident registered incidence, there was an accumulated pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Today, when the literature is so abundant, research quality and possible biases should be taken into account defining inclusion criteria for studies into pooled analyses, meta-analyses and reviews. For example, certain reports on Chernobyl-related thyroid cancer can be conductive to over-estimation of carcinogenic properties of radioiodine; discussed in [72].…”
Section: Discussion Around Dose and Dose Rate Effectiveness Factor (Dmentioning
confidence: 99%
“…Today, when the literature is so abundant, research quality and possible biases should be taken into account defining inclusion criteria for studies into pooled analyses, meta-analyses and reviews. For example, certain reports on Chernobyl-related thyroid cancer can be conductive to over-estimation of carcinogenic properties of radioiodine; discussed in [72].…”
Section: Discussion Around Dose and Dose Rate Effectiveness Factor (Dmentioning
confidence: 99%
“…The above and previously published [6,7,12,47] arguments question in principle the cause-effect relationship between ionizing radiation and cancer incidence increase after the CA. With regard to pediatric TC, existence of radiogenic cases cannot be excluded, but the registered incidence increase was largely caused by factors other than radiation.…”
Section: Introductionmentioning
confidence: 85%
“…The registered incidence of pediatric TC in the former Soviet Union (SU) before the accident was low compared to other developed nations, which had obviously been caused by differences in diagnostic quality and coverage of the population by medical examinations [7]. Accordingly, there was a pool of undiagnosed TC prior to the accident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive screening, false positives, and detection of previously neglected tumors may have led to overestimation of Chernobyl-associated PTC and tumor aggressivity. 23 Increases in neither anaplastic nor poorly differentiated carcinomas are found in elderly adults who underwent childhood tonsillar or thymic irradiation. Most studies have not found thyroid cancer following external beam irradiation to be more aggressive.…”
Section: Is Ptc a Common Childhood Phenomenon?mentioning
confidence: 99%